2017
DOI: 10.18553/jmcp.2016.16233
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Treatment in Prostate Cancer Patients Treated with Abiraterone Acetate or Enzalutamide

Abstract: This research was funded by Janssen Scientific Affairs. Pilon, Emond, and Lefebvre are employees of Analysis Group, a consulting company that has received research grants from Janssen Scientific Affairs. Behl and Ellis are employees of Janssen Scientific Affairs and stockholders in Johnson & Johnson. Dawson is on the speakers bureau for Janssen, Astellas, and Sanofi Aventis. Emond reports grants from Regeneron, Bristol-Myers Squibb, GlaxoSmithKline, Aegerion, Bayer, Novartis, Allergan, Millenium, and Genentech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
1
10
2
6
Order By: Relevance
“…Two recent administrative claims studies found conflicting results with the current study, reporting that treatment duration with abiraterone acetate was higher than with enzalutamide among overall populations of patients with prostate cancer or mCRPC [ 7 , 17 ]. Pilon et al [ 7 ] reported that the duration of overall prostate cancer treatment was significantly longer among patients who initiated abiraterone acetate compared with those who initiated enzalutamide, and a second study by Behl et al [ 17 ] reported that patients who initiated abiraterone acetate had higher medication adherence than those who initiated enzalutamide. However, Pilon et al and Behl et al did not differentiate between chemotherapy-naïve and post-chemotherapy patients—two patient groups with distinct disease characteristics and severity.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Two recent administrative claims studies found conflicting results with the current study, reporting that treatment duration with abiraterone acetate was higher than with enzalutamide among overall populations of patients with prostate cancer or mCRPC [ 7 , 17 ]. Pilon et al [ 7 ] reported that the duration of overall prostate cancer treatment was significantly longer among patients who initiated abiraterone acetate compared with those who initiated enzalutamide, and a second study by Behl et al [ 17 ] reported that patients who initiated abiraterone acetate had higher medication adherence than those who initiated enzalutamide. However, Pilon et al and Behl et al did not differentiate between chemotherapy-naïve and post-chemotherapy patients—two patient groups with distinct disease characteristics and severity.…”
Section: Discussioncontrasting
confidence: 74%
“…Until 2010, treatments of mCRPC were primarily limited to taxane chemotherapy (docetaxel) or oral non-steroidal anti-androgen therapy plus luteinizing hormone-releasing hormone analogs [ 6 ]. Recently, there have been many advances in treatment options, including novel taxane chemotherapy (e.g., cabazitaxel), immunotherapy (e.g., sipuleucel-T), radiotherapy (e.g., radium-223), and novel hormonal therapy (e.g., enzalutamide and abiraterone acetate) [ 7 ]. These new treatments have greatly extended the median overall survival of patients with mCRPC (ranging from approximately 9–18 months in 2010 to 16–35 months in 2016), depending on tumor burden [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the generalizability of our findings to patients with better general health status and earlier disease stages may be limited. However, real-world studies from other countries on less co-morbid mCRPC patients being at an early disease stage have shown comparable low discontinuation and non-adherence rates [ 7 , 24 , 25 ]. Our specific AEM probably does not limit the generalizability of the results [ 26 ] since findings from other studies on the effectiveness of AEM for patients taking oral-anti-cancer agents are similar across different countries and settings: recently published systematic reviews have found little to no impact for most educational AEM as well as reminder components [ 10 , 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allgemein ist eine längere primäre ADT-Dauer mit einer längeren AA + P-Therapie verbunden [15,16]. In der vorliegenden Studie war die Dauer der AA + P-Therapie für FTh-im Vergleich zu STh-Patienten nur geringfügig kürzer und die AA + P-Behandlungsdauer war vergleichbar mit der in anderen ‚Real-World'-Studien [17,18]. Hauptgrund für den Start der AA + P-Therapie war biochemische Progression und für das Therapieende die Progression im Allgemeinen oder der Tod.…”
Section: Diskussionunclassified